Maternal and Perinatal Outcomes of Oligohydramnios in Pregnancies at A Tertiary Care Hospital in Bangladesh (Sir Salimullah Medical College Journal, 2026)
Background: Oligohydramnios is one of the important complications seen in pregnancy. It increases the chance of miscarriage, premature birth, meconium aspiration syndrome, RDS, still birth, low birth weight baby & operative intervention for oligohydramnios on pregnancy out come. Methods: This cross sectional study was conducted in department of Obstetrics &Gynaecology, Sir Salimullah Medical College Mitford Hospital, Dhaka during the period of January 2022 to June 2022 among 50 patients to assess the effect of oligohydramnios on pregnancy outcome and to formulate the plan of management in order to reduce the related complications. Clinically suspected oligohydramnios was confirmed by USG. Age, parity, gestational age, mode of delivery, colour of liquor, Apgar score, birth weight, neonatal complications were recorded at time of delivery. Results: The socio demographic data revealed that 58% respondents were primigravida, mean age was 23.96±5.01 SD (Range 18-40), gestational age was e”37 weeks in 90% cases. 64% respondents were diagnosed as severe oligohydramnios. Meconium stained liquor and the rate of caesarean section was higher in severe oligohydramnios was associated with low Apgar score (